Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(3x+4):12+17=19
=>3x+4:12=19-17
=>(3x+4):12=2
=>3x+4=2x12
=>3x+4=24
=>3x=24-4
=>3x=20
=>x=20/3
tíc mình nha
a, ( 4x - 13 ) - (3x + 17) = -19 - (-12)
=> 4x - 13 - 3x - 17 = -19 + 12
=> x = -19 + 12 + 13 + 17 = 23
( 4x - 13 ) - (3x + 17) = -19 - (-12)
4x - 13- 3x - 17= -7
(4x-3x)-13=-7
x-13=-7
x=-7 +13
x=6
Câu 1:
\(3x+17=12\)
\(\Leftrightarrow3x=12-17\)
\(\Leftrightarrow3x=-5\)
\(\Leftrightarrow x=-\frac{5}{3}\)
Câu 2:
\(1+\left(-2\right)+3+\left(-4\right)+...+19+\left(-20\right)\)
\(=\left[\left(-1\right)+2\right]\left(20:2\right)\)
\(=-10\)
Tìm x :
3x+17=12
3x=12-17
3x=-5
x=\(\frac{-5}{3}\)
Vậy x=\(\frac{-5}{3}\)
Tính tổng :
1+(-2)+3+(-4)+...+19+(-20)
=1-2+3-4+...+19-20
=(1-2)+(3-4)+...+(19-20) (có tất cả 10 cặp)
=(-1)+(-1)+...+(-1)
=(-1).10=-10
Tìm số nguyên x, biết:
1) -16 + 23 + x = - 16
7+x=-16
x=-16-7
x=-23
2) 2x – 35 = 15
2x=15+35
2x=50
x=50:2
x=25
3) 3x + 17 = 12
3x=12-17
3x=-5
x=-5/3
4) (2x – 5) + 17 = 6
2x-5=6-17
2x-5=-11
2x=-11+5
2x=-6
x=-6:2
x=-3
5) 10 – 2(4 – 3x) = -4
2(4-3x)=10-(-4)
2(4-3x)=14
4-3x=14:2
4-3x=7
3x=4-7
3x=-3
x=-3:3
x=-1
6) - 12 + 3(-x + 7) = -18
3(-x+7)=-18-(-12)
3(x+7)=-6
x+7=-6:3
x+7=-2
x=-2-7
x=-9
-3-2x+17=12-3x
-2x+3x=12-17+3
x=-2
b.43-2x-2=-48+x
-2x-x = -48+2-43
-3x=-89
x=-89/-3
c -253-2x=102+19-x
-2x+x=102+19+253
-x=374
x=-374
a)
13/4+x=2
x=2-13/4
x=-5/4
b)
2x.17/12=3/7
2x =3/7;17/12
2x =36/119
x =36/119 : 2
x =18/119
c)
2x.17/12=19/7
2x =19/7:17/12
2x =228/119
x =228/119;2
x =114/119
d)
1/2x + 5/6=-3
1/2x =-3-5/6
1/2x =-23/6
x =-23/6:1/2
x =-23/3
a) 4(x+1)-(3x+1)=14
<=>4x+4-3x-1=14
<=>4x-3x = 14-4
<=>x=10
b) -12(x-5) +7.(3x)=5
<=> -12x +60 + 21+7x=5
<=> -12x+7x=5-60-21
<=> -5x=-76
<=> x=76/5
c) 17x + 34 -4x+28-9x=82
<=> 17x-9x-4x=82-34-28
<=> 4x=20
<=> x=5
(3x + 4) : 12 + 17 = 19
(3x + 4) : 12 = 2
3x + 4 = 24
3x = 20
x = 20/3
( 3x + 4 ) : 12 + 17 = 19
( 3x + 4 ) : 12 = 19 - 17
( 3x + 4 ) : 12 = 2
3x + 4 = 2.12
3x + 4 = 24
3x = 24 - 4
3x = 20
x = 20 : 3
x = 6,66...
Đáp số : 6,66...